Comparison of anti-retroviral therapy treatment strategies in prevention of mother-to-child transmission in a teaching hospital in Ethiopia - Kumela K; Amenu D; Chelkeba L (Centro de Investigaciones y Publicaciones Farmaceuticas, 2015)
Background: More than 90% of Human immunodeficiency virus (HIV) infection in children is acquired due to mother-to-child transmission, which is spreading during pregnancy, delivery or breastfeeding. Objective: To determine the effectiveness of highly active antiretroviral and short course antiretroviral regimens in prevention of mother-to-child transmission of HIV and associated factors Jimma University Specialized Hospital (JUSH). Method: A hospital based retrospective cohort study was conducted on HIV infected pregnant mothers who gave birth and had follow up at anti-retroviral therapy (ART) clinic for at least 6 months during a time period paired with their infants. The primary and secondary outcomes were rate of infant infection by HIV at 6 weeks and 6 months respectively. The Chi-square was used for the comparison of categorical data multivariate logistic regression model was used to identify the determinants of early mother-to-child transmission of HIV at 6 weeks. Cox proportional hazard model was used to analyze factors that affect the 6 month HIV free survival of infants born to HIV infected mothers. Results: A total of 180 mother infant pairs were considered for the final analysis, 90(50%) mothers received single dose nevirapine (sdNVP) designated as regimen-3, 67 (37.2%) mothers were on different types of ARV regimens commonly AZT + 3TC + NVP (regimen-1), while the rest 23 (12.8%) mothers were on short course dual regimen AZT + 3TC + sdNVP (regimen-2). Early mother-to-child transmission rate at 6 weeks for regimens 1, 2 and 3 were 5.9% (4/67), 8.6% (2/23), and 15.5% (14/90) respectively. The late cumulative mother-to-child transmission rate of HIV at 6 months regardless of regimen type was 15.5% (28/180). Postnatal transmission at 6 months was 28.5% (8/28) of infected children. Factors that were found to be associated with high risk of early mother-to-child transmission of HIV include duration of ARV regimen shorter than 2 months during pregnancy (OR=4.3, 95%CI =1.38-13.46), base line CD4 less than 350 cells/cubic mm (OR=6.98, 95%CI=0.91-53.76), early infant infection (OR=5.4, 95%CI=2.04-14.4), infants delivered home (OR=13.1, 95%CI=2.69-63.7), infant with birth weight less than 2500 g (OR=6.41, 95%CI=2.21-18.61), and mixed infant feeding (OR=6.7, 95%CI=2.2-20.4). Antiretroviral regimen duration less than 2 months, maternal base line CD4 less than 350 cells/cubic mm and mixed infant feeding were also important risk factors for late infant infection or death. Conclusion: The effectiveness of multiple antiretroviral drugs in prevention of early mother-to-child transmission of HIV was found to be more effective than that of single dose nevirapine, although, the difference was not statistically significant. But in late transmission, a significant difference was observed in which infants born to mother who received multiple antiretroviral drugs were less likely to progress to infection or death than infants born to mothers who received single dose nevirapine.